Helicobacter pylori Infection Is Associated With Thyroid Dysfunction in Children With Congenital Hypothyroidism - Ivani Novato Silva; Lara Vieira Marçal; Dulciene Maria Magalhães Queiroz (Frontiers Media S.A., 2022)
Helicobacter pylori (H. pylori) infection leads to a systemic low-grade inflammatory state and has been associated causally with a diverse spectrum of extra-gastric disorders. Among them, the infection has been involved in the pathogenesis of autoimmune thyroid disease (ATD), but only one study had evaluated children. Therefore, a cross-sectional study was conducted in a cohort of 142 children and adolescents, randomly assessed among those followed up for thyroid diseases in a university pediatric endocrinology service: 106 with congenital hypothyroidism (CH) and 36 with ATD. All children were asymptomatic, under strict control on levothyroxine replacement, and reported no other diseases or use of drugs. Helicobacter pylori status was evaluated by the 13C-Urea Breath Test (13C-UBT). Antithyroid antibodies (ATPO, antiTg, and TRAb) and serum thyroid hormones (TSH, free T4, and T3) were assessed by standard assays. Data were analyzed in logistic models by the SPSS statistical software package, and a p-value ≤ 0.05 was considered statistically significant. The prevalence of H. pylori infection was 19.44% in children with ATD. Neither the gender nor the serum levels of thyroid hormones and antithyroid antibodies were associated with the H. pylori-positive status. Thirty-seven (34.90%) children with CH were infected with H. pylori. The mean T3 serum level (3.59 ± 0.84) was significantly lower (p = 0.001) in the infected children than in those free from the infection (3.95 ± 0.89), association that remained after adjustment for the other variables in the multivariate analysis. Because no difference was observed in the levels of TSH and T4, the results indicate that the infection may lead to impairment in the thyroid hormonal balance, but not in the hypothalamic-pituitary-thyroid axis function. In as much as H. pylori infection is highly widespread and the prevalence of CH is also not negligible, additional studies are required to confirm our results and to identify the involved mechanisms.